Prevalence and assessment of the risk factors of stress urinary incontinence in gynaecology out patients in a tertiary care centre - Bora, Ananya; Gupta, Alka S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Stress urinary incontinence (SUI) is the complaint of involuntary leakage of urine during increased abdominal pressure in the absence of detrusor contraction. Although not a life-threatening condition, stress urinary incontinence causes various physical, psychological, and sexual problems for millions of women and their families. Although these conditions are highly prevalent, they are not often reported by patients. This was the reason for the study; to find out the prevalence and the associated risk factors. Methods: A total of 400 patients presenting in the gynaecology outpatient department with various complaints were studied. A detailed history was taken, and examination was done. Urine microscopy and culture studies were done and whenever found positive; the infection was treated. Bonney’s test was done on full bladder. Results: Stress urinary incontinence was diagnosed in 41 (10.30%) of the women. The most common co morbidity was found to be tuberculosis and other lung diseases. Among the study population, 4% of women had culture positive urinary tract infection. Conclusions: Stress urinary incontinence was seen in 10.30% of the study population. It was seen more commonly among the elderly. Urine routine and microscopy was done for all patients complaining of leakage of urine or any other urinary complaints.